Heat shock regulatory elements are present in telomeric repeats of Chironomus thummi - Martinez, Jose Luis (Oxford University Press, 2001)
As in other Diptera, the telomeres of Chironomus thummi lack canonical short telomerase-specified repeats and instead contain complex sequences. They react to heat shock and other stress treatments by forming giant puffs at some chromosome termini, which are visible in polytene cells. All telomeres, except the telocentric end of chromosome four (4L), consist of large blocks of repeats, 176 bp in length. Three subfamilies of telomeric sequences have been found to show different distribution patterns between chromosome ends. TsA and TsC are characteristic of telomeres 3R and 4R, respectively, whereas TsB is present in the other non-telocentric telomeres. Heat shock transcription regulatory elements have been identified in the telomeric sequences, appearing differentially represented in the three subfamilies, but otherwise rather similar in size and sequence. Interestingly, TsA and TsB repeats share the well-conserved heat shock element (HSE) and GAGA motif, while the TATA box is only present in the former. Neither a HSE nor a TATA box appear in TsC repeats. Moreover, experimental data indicate that the HSE is functionally active in binding heat shock transcription factor (HSF). These results provide, for the first time, a molecular basis for the effect of heat shock on C.thummi telomeres and might also explain the different behaviour they show. A positive correlation between the presence of HSE and telomeric puffing and transcription under heat shock was demonstrated. This was also confirmed in the sibling species Chironomus piger. The significance of heat shock activation of telomeric repeats in relation to telomeric function is unknown at present, but it might be compared to the behaviour of other non-heat shock protein coding sequences, such as SINE-like and LINE-like retroelements, which have been reported to be activated by stress.